Melatonin Alleviates Neonatal Necrotizing Enterocolitis by Repressing the Activation of the NLRP3 Inflammasome - Xiaoyu Xiong; Zhongkun Bao; Yanhong Mi; Xinhong Wang; Jiajun Zhu (Gastroenterology Research and Practice)
Objective. Necrotizing enterocolitis (NEC) is one of the commonest gastrointestinal critical diseases in newborns. Several researches have proven the efficacy of melatonin (MEL) on NEC, but the latent mechanisms were ambiguous. We designed the current research to evaluate the function and mechanism of MEL on NEC in a neonatal mouse model. Methods. The newborn mice were subjected to formula milk containing LPS and hypoxia to establish a NEC model and also intraperitoneally injected with MEL. During the experiment, all mice were closely monitored and weighed. The effect of MEL on the histopathological injury of the terminal ileum tissues, inflammation, and oxidative stress of serum in NEC mice was examined by hematoxylin-eosin (H&E) staining and ELISA. The effect of MEL on the NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome was assessed via quantitative real-time PCR and Western blot. Results. MEL intensified the survival rate and body weight in NEC mice. The H&E staining illustrated that MEL improved the histopathological injury in NEC mice. Moreover, MEL repressed the IL-1β, TNF-α, and MDA levels of serum and enhanced the SOD and GSH-Px levels of serum in NEC mice. We also discovered that MEL attenuated the mRNA and protein levels of NLRP3, Toll-like Receptor 4 (TLR4), NF-κB, and caspase-1 of the terminal ileum tissues in NEC mice. Conclusion. Our research illuminated that MEL attenuated the severity of NEC via weakening the activation of the NLRP3 inflammasome.